RGDS-Modified Superporous Poly(2-Hydroxyethyl Methacrylate)-Based Scaffolds as 3D In Vitro Leukemia Model - Svozilová, Hana; Plichta, Zdeněk; Proks, Vladimír; Studená, Radana; Baloun, Jiří; Doubek, Michael; Pospíšilová, Šárka; Horák, Daniel (International journal of molecular sciences, 2021)
Superporous poly(2-hydroxyethyl methacrylate-co-2-aminoethyl methacrylate) (P(HEMA-AEMA)) hydrogel scaffolds are designed for in vitro 3D culturing of leukemic B cells. Hydrogel porosity, which influences cell functions and growth, is introduced by adding ammonium oxalate needle-like crystals in the polymerization mixture. To improve cell vitality, cell-adhesive Arg-Gly-Asp-Ser (RGDS) peptide is immobilized on the N-(γ-maleimidobutyryloxy)succinimide-activated P(HEMA-AEMA) hydrogels via reaction of SH with maleimide groups. This modification is especially suitable for the survival of primary chronic lymphocytic leukemia cells (B-CLLs) in 3D cell culture. No other tested stimuli (interleukin-4, CD40 ligand, or shaking) can further improve B-CLL survival or metabolic activity. Both unmodified and RGDS-modified P(HEMA-AEMA) scaffolds serve as a long-term (70 days) 3D culture platforms for HS-5 and M2-10B4 bone marrow stromal cell lines and MEC-1 and HG-3 B-CLL cell lines, although the adherent cells retain their physiological morphologies, preferably on RGDS-modified hydrogels. Moreover, the porosity of hydrogels allows direct cell lysis, followed by efficient DNA isolation from the 3D-cultured cells. P(HEMA-AEMA)-RGDS thus serves as a suitable 3D in vitro leukemia model that enables molecular and metabolic assays and allows imaging of cell morphology, interactions, and migration by confocal microscopy. Such applications can prospectively assist in testing of drugs to treat this frequently recurring or refractory cancer.
Keywords: nádorové buněčné linie; tkáňové podpůrné struktury; Oligopeptides; Cell Culture Techniques; hydrogely; oligopeptidy; poréznost; Mesenchymal Stem Cells; Cell Line, Tumor; 3D scaffold; Tissue Scaffolds; mezenchymální kmenové buňky; chronická lymfatická leukemie; sukcinimidy; Hydrogels; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Porosity; chronic lymphocytic leukemia; poly(2-hydroxyethyl methacrylate); buněčné kultury; B cell survival; Succinimides; RGDS; lidé